If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = 53 Reorder the terms: 9 + 4x = 53 Solving 9 + 4x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4x = 53 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 53 + -9 4x = 53 + -9 Combine like terms: 53 + -9 = 44 4x = 44 Divide each side by '4'. x = 11 Simplifying x = 11
| 9h-6=42 | | 3x=-16-4y | | -2x=-5x+3 | | x-6-2x=x | | 4-15m=-64 | | m^3n^3-64=0 | | 2w+70=3w | | 30x^2+2x-1=0 | | -2x-3x=x | | 3(p+1)=6 | | 4x-8+x=18-7 | | -(3xy-12)+3(4xy+6)= | | -4n-1=5+5(5n-7) | | 4(k+5)=15+4k | | 2(c+1)c=4 | | -4+5n=18+3n | | 50=7.50x+6.95 | | 6-2x=6x-10+6 | | 5x-30=11x+12-3x | | 5x-17=-3(3-2x) | | 4*(2x-5)=3-(2x+1) | | 144=-6k | | 5n-45=7n-28 | | 9b-10=-6-18 | | -k-(-9k)-11+2k-4= | | 4m-1+1=m | | x-7x=-12 | | 15x-100=10 | | 12=2(4u-3)-2(5u-1)-6 | | y^3-3y= | | -3(-7b+2)=90 | | 5(4x-3)=37+7x |